Structural Connectivity of the Anterior Cingulate Cortex, Claustrum, and the Anterior Insula of the Mouse - Qadir, Houman; Krimmel, Samuel R.; Mu, Chaoqi; Poulopoulos, Alexandros; Seminowicz, David A.; Mathur, Brian N. (Frontiers in Neuroanatomy, 2018)
The claustrum is a narrow subcortical brain structure that resides between the striatum and insular cortex. The function of the claustrum is not fully described, and while our previous work supports a role for the claustrum in top-down cognitive control of action, other evidence suggests the claustrum may be involved in detecting salient changes in the external environment. The anterior cingulate cortex (ACC) and the anterior insular (aINS) are the two major participants in the salience network of human brain regions that activate in response to salient stimuli. While bidirectional connections between the ACC and the claustrum exist from mouse to non-human primate, the aINS connectivity with claustrum remains unclear, particularly in mouse. Here, we explored structural connections of the aINS with the claustrum and ACC through adeno-associated virus (AAV) neuronal tract tracer injections into the ACC and aINS of the mouse. We detected sparse projections from the claustrum to the aINS diffuse projections from the aINS to the borders of the claustrum were observed in some cases. In contrast, the insular cortex and endopiriform nucleus surrounding the claustrum had rich interconnectivity with aINS. Additionally, we observed a modest interconnectivity between ACC and the aINS. These data support the idea that claustrum neuron responses to salient stimuli may be driven by the ACC rather than the aINS.